IDENTIFIKASI DAN ANALISIS PENINGKATAN TINGKAT ENGAGEMENT PEGAWAI FAKULTAS EKONOMI UNSOED: SIKAP POSITIF PEGAWAI DAN ORGANISASI (KOMITMEN, KETERIKATAN, KETERLIBATAN) DALAM PENCAPAIAN KEBERHASILAN ORGANISASI - Yunanto, Ary; Daryono, Daryono (Performance, 2011)
Employee statifaction at the moment assumed less enough for organization to subsidize employee performance. for that's need employee engagement. employee engagement are some involvement, commitment, willing and sense of belonging towards job and organization. This research need to found degree employee engagement at Ekonomi Faculty of University Jenderal Soedirman. This research use survey method to measures level employee engagement, with three three dimensions engagement which are, organization dimension, job dimension, opportunity and growth dimension. This research have result total Employee engagement is 3.15, with with the highest level degree is employee engagement Job dimension, then followed with dimension employee engagement opportunity and growth, and employee engagement organization dimension level has lower degree.